2021
DOI: 10.3389/fmicb.2021.696398
|View full text |Cite
|
Sign up to set email alerts
|

The Microbiome of the Medicinal Plants Achillea millefolium L. and Hamamelis virginiana L.

Abstract: In the recent past many studies investigated the microbiome of plants including several medicinal plants (MP). Microbial communities of the associated soil, rhizosphere and the above-ground organs were included, but there is still limited information on their seasonal development, and in particular simultaneous investigations of different plant organs are lacking. Many studies predominantly addressed either the prokaryotic or fungal microbiome. A distinction of epi- and endophytic communities of above-ground p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 102 publications
(206 reference statements)
1
10
0
Order By: Relevance
“…Another core taxon observed in both the fructoplane and SE pulp of ‘Hass’ avocado, R. mucilaginosa , was previously reported to promote plant growth and seed germination in a bioassay using Brassica juncea (Ramos‐Garza et al, 2015). We further observed that there was a decrease in numbers of core taxa from the epiphytic (16) to endophytic (6) compartments of the ‘Hass’ avocado fruit and this is similar to the findings of Sauer et al (2021) on Achillea leaves. Despite not being dominant in the SE pulp at all of the six avocado postharvest stages in the present study, the potential SER‐causing genera, Neofussicocum , Fusarium , Penicillium and Epicoccum were all present in very high abundances at the ripe and ready‐to‐eat stage, which is a critical point in pathogen infection.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…Another core taxon observed in both the fructoplane and SE pulp of ‘Hass’ avocado, R. mucilaginosa , was previously reported to promote plant growth and seed germination in a bioassay using Brassica juncea (Ramos‐Garza et al, 2015). We further observed that there was a decrease in numbers of core taxa from the epiphytic (16) to endophytic (6) compartments of the ‘Hass’ avocado fruit and this is similar to the findings of Sauer et al (2021) on Achillea leaves. Despite not being dominant in the SE pulp at all of the six avocado postharvest stages in the present study, the potential SER‐causing genera, Neofussicocum , Fusarium , Penicillium and Epicoccum were all present in very high abundances at the ripe and ready‐to‐eat stage, which is a critical point in pathogen infection.…”
Section: Discussionsupporting
confidence: 90%
“…Amongst these core taxa were members of the Ascomycota phylum including Cladosporium, Neofussicocum, Fusarium, Penicillium and Epicoccum, which were previously described as SER causing genera in avocado (Fourie & Coertzen, 2018;Valencia et al, 2019;Wanjiku et al, 2021). The core communities tend to be comprised of key microbial taxa that play an essential role in the health and fitness of the plant holobiont (Lemanceau et al, 2017;Sauer et al, 2021),…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The microbiota of medicinal plants is an important factor affecting the health and productivity of the host ( Maggini et al, 2020 ), and can be directly or indirectly involved in the production of biologically active compounds by the host ( Koberl et al, 2013 ). The medicinal plant-associated microbiota has been gradually characterized with the omics technology ( Chen et al, 2018 ; Ulloa-Muñoz et al, 2020 ; Dong et al, 2021c ; Sauer et al, 2021 ). However, the mechanism of medicinal plant-associated microbiota construction and the phenotype and function of the core microbiota have yet to be elucidated.…”
Section: Discussionmentioning
confidence: 99%